Checklist of the planktonic rotifer fauna in the active floodplain area of the Danube (1843-1806, 1669 and 1437-1489 rkm) - Schöll, K.; Kiss, A. (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2009)
A checklist of Rotifera containing 84 taxa from the main arm and the active floodplain of the River Danube is provided. Beauchampiella eudactylota Gosse, 1886; Brachionus forficula forficula (Wierzejski, 1891); Brachionus quadridentatus mirabilis (Daday, 1897) and Conochilus dossuarius dossuarius (Hudson, 1875) are new to the fauna of th Danube. Brachionus angularis aestivus Skorikov, 1914; Brachionus budapestiensis punctatus (Hempel, 1896) and Filinia passa (O. F. Müller, 1786) are new to the Hungarian section of the Danube.